Primary sutureless repair concomitant with the Warden procedure. (February 2023) - Watanabe, Seito; Nakata, Tomohiro; Suehiro, Syoichi; Yasuda, Kenji; Nakashima, Shigeki; Oda, Teiji
A 2-month-old girl who had supracardiac total anomalous pulmonary venous connection (Darling classification type 1b) was referred to our institution. Computed tomography showed that multiple right upper pulmonary veins drained into the vertical vein, near the entry to the superior vena cava. The common pulmonary venous chamber was located lower right than usual, and right upper pulmonary veins were far from the common chamber. We successfully performed primary sutureless repair concomitant with the Warden procedure. Postoperative computed tomography showed unobstructed pulmonary veins and superior vena cava routes, and the vertical vein between right upper and lower pulmonary veins shrank slightly.